2022
DOI: 10.4097/kja.21096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postoperative non-steroidal anti-inflammatory drugs on anastomotic leakage after pancreaticoduodenectomy

Abstract: This article has been accepted for publication and has undergone full peer review but has notbeen through the copyediting, typesetting, pagination, and proofreading processes, which may lead to differences between this version and the version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The study exploring postoperative NSAIDs with the highest number of PD patients found that NSAIDs were associated with significantly greater CR-POPF [80]. In smaller studies considering non-selective NSAIDs, no difference in CR-POPF was reported after PD [81][82][83][84], even in high-risk (>40% acinar cell density) patients [76].…”
Section: Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…The study exploring postoperative NSAIDs with the highest number of PD patients found that NSAIDs were associated with significantly greater CR-POPF [80]. In smaller studies considering non-selective NSAIDs, no difference in CR-POPF was reported after PD [81][82][83][84], even in high-risk (>40% acinar cell density) patients [76].…”
Section: Analgesiamentioning
confidence: 99%
“…As such, the effect of nonselective NSAIDs on particular pancreatectomy patients requires further clarification in larger, cohort-specific RCTs. Moreover, as non-selective NSAIDs may impair angiogenesis and collagen deposition critical for wound healing, they should be used cautiously, with alternatives preferred if possible [80]. This also applies to COX-2 selective inhibitors associated with CR-POPF, even at low doses [81].…”
Section: Analgesiamentioning
confidence: 99%
“…However, the overall incidence of HL was too low (1.9%) to allow for the role of NSAIDs to be analyzed as a risk factor for postoperative HL using binary logistic regression analysis. In addition, NSAID use was not a risk factor for POPF in that study [ 24 ].…”
mentioning
confidence: 98%
“…Yoon et al [ 24 ] retrospectively investigated the association between postoperative NSAID use and clinically relevant postoperative anastomotic leakage (postoperative pancreatic fistula [POPF] or hepatojejunostomy anastomotic leakage [HL]), in > 4,000 patients. The authors found a higher incidence of HL within the first 5 postoperative days in the group that received NSAIDs postoperatively (OR: 3.11, 95% CI [1.86, 5.21]).…”
mentioning
confidence: 99%